(untitled) (International Current Pharmaceutical Journal, 2014)
The main aim of the present research was to develop a fast dissolving oral polymeric film with good mechanical properties, faster disintegration and dissolution when placed on tongue. Donepezil hydrochloride (DPH) is prescribed in the treatment of mild to moderate Alzheimers disease (AD). The polymers selected for preparing films were sodium alginate (SA), poly vinyl alcohol (PVA) and guar gum (GG). Three batches of films were prepared by solvent casting method with sodium alginate, sodium alginate & PVA and with the combination of sodium alginate & guar gum. From these three batches, three optimized film formulations S3, SP7 and SG8 were selected based on disintegration time. To these three selected film formulations, superdisintegrants sodium starch glycolate (SSG), cross carmellose sodium (CCS) and cross povidone (CP) were added at a concentration of 4% w/w of polymer to improve the disintegration time. The films prepared with or without superdisintegrants were compared for fast releasing properties. Based on DT and in vitro dissolution data, S3CP was selected as the best formulation among the all formulations. DOI: http://dx.doi.org/10.3329/icpj.v3i3.17892 International Current Pharmaceutical Journal, February 2014, 3(3): 243-246